Strategic networking in the technical hei‘s of the Baltic sea region - Nugaras, Justas (Business, Management and Economics Engineering, 2012)
This paper presents the results of the empirical research of the networking of Technical Higher Education Institutions (HEI‘S) of the Baltic Sea region. The research was conducted in order to understand how the Social Network Analysis (SNA) and network mapping methods could help to strengthen institution’s strategic perspective through networking. The author analyse the interaction phenomena in the Higher education sector; its’ impact for networking of institutions and for the network itself; the role of the position in the networks; abilities to strengthen the node’s perception of the network for the strategizing purposes. The research was based on the SNA of the Erasmus programme student mobility data. The results of the research cover the implications of aspects of the network centrality, clustering and ego networks let to identify the node’s position in the network, and to understand surrounding network. The research disclosed that the SNA could be applied in supporting the strategizing process by: increasing of understanding of embedded networks, having more realistic network picture, also could be used as supplement evaluation and development planning method for the relationships portfolio management for HEI’s.